Переваги та недоліки розрахунку гранично-допустимого скиду речовин за басейновим принципом - Петренко, Олексій Сергійович (КНУБА, 2013)
Показано вплив в річці процесів розбавлення та самоочищення на концентрацію формальдегіду. Представлена послідовність розрахунків граничнодопустимої скидної концентрації та маси речовини за басейновим принципом. Наведено результати аналізу його переваг і недоліків в порівнянні з локальним принципом розрахунку. Показано влияние в реке процессов разбавления и самоочищения на концентрацию формальдегида. Представлена последовательность расчётов гранично-допустимой сбросной концентрации и массы вещества по бассейновому принципу. Приведены результаты анализа его преимуществ и недостатков в сравнении с локальным принципом расчёта. The article deals with the influence of the river dilution and self-purification process on the concentration of formaldehyde. The sequence of calculations of the maximum allowable discharge concentration and mass of substance is presented. Conclusion on advantages and insufficiencies of such approach is given as compared to the local management principle of computation.
Advantages and insufficiencies of maximum allowable discharge of substances computation in accordance with watershed management principle
Преимущества и недостатки расчета гранично-допустимого сброса веществ в соответствии с бассейновым принципом
Keywords: скид стічних вод; допустима скидна концентрація; розбавлення; самоочищення; басейновий та локальний принцип розрахунку; сброс сточных вод; допустимая сбросная концентрация; разбавление; самоочищение; бассейновый и локальный принцип расчёта; waste water discharge; maximum allowable discharge concentration; dilution; self-purification; watershed management and local management principles of computation